Bird assessment along the mangrove coastal area of Brgy. Tagpuro, Tacloban City. - Montajes, Phoebe Joyce R. (Phoebe Joyce R. Montajes, 2018)
The Philippines is considered to be a biodiversity hotspot catering to a wide variety of species of plants and animals; some of these species are endemic to the country. However, last November 2013 typhoon Haiyan heavily devastated Tacloban City and it led to the loss of natural habitat and caused the migration of some species living in the ecosystem. One of the affected habitats was the mangrove area. To assess the environmental condition, the presence of birds in the area was used as bioindicators. Birds are dependent on the habitat functioning in specific ways, the population trends of birds can tell how well the ecosystem functions. To analyze the bird diversity, Menhinick's, Shannon-Weiner's and Pielou's Evenness indices were used. Four strategic points were established. A 20-minute survey in each station point was conducted. Observations were recorded using bulls-eye and standardized frequency data sheets. A bird expert identified and confirmed the bird species observed. To supplement the identification of bird species, a spotting scope with a camera attached to its eyepiece was used. There were a total of 632 individuals, 21 species belonging to 15 families were observed, and most abundant species found was C. troglodyte. The bird communities found in the study site are classified as those that can highly adapt with human settlement. This study shows that Tagpuro mangrove site proved to be a suitable habitat to bird species among other wildlife and has the potential for ecotourism on bird watching.